APPROACH TO PAIN PREVENTION AMONG INFANTS DURING VACCINATION - A.A. Stepanov; G.V. Yatsyk; L.S. Namazova (Union of pediatricians of Russia, 2007)
The main focus of the research in this article is the approach whixh gives an oppeortunity to humanize the medical procedures for prevention of the negative effects of pain in infants. The article presents information on the estimate of pain reaction among infants during the scheduled vaccination against Hepatitis type B. The authors described the application experience this manipulation pain relief with the skin application of the local anesthetic Emla (Astrazeneca AB, Sweden). Key words: pain relief, pain, painpain estimate, vaccination, children.